Blind balustrades at Sir H.C Dinshaw building - Ghosh, Ayan (2023)
Blind balustrades on the facade of Sir H.C. Dinshaw Building with wave motif band running below. Blind balustrades feature in every building in the Horniman Circle. Their purpose is decorative, rather than having any utilitarian function, unlike real balustrades, which provide support and provide protection along a ledge or a staircase.